Unemployment and Economic Consequences: Case Study on the Financial Burden in Gasabo District, Kigali – Rwanda - Umulisa, Annah (Digital Repository of Theses, 2025)
This research study investigated the financial burdens faced by unemployed households, specifically seven core financial burdens. A descriptive survey design was used, with data collected through distributed questionnaires from a sample of 240 unemployed households. Findings show that the primary financial burden in the sampled unemployed households is family responsibilities (37.39%), the second is daily living expenses (18.26%), the third is debt (17.83%), the fourth is housing (15.65%) and the fifth is education which accounts for 10.87% of the financial burden, on the other side healthcare was not reported as a significant concern due to high health insurance coverage and health policy where health facilities are decentralized to the level of village under the support of volunteers (Abajyanama b’ubuzima) and health posts to the cell level. Income sources during unemployment vary by age group, where young households rely mainly on family support and informal work, while older groups of households depend mostly on savings and government assistance. This study provided the economic consequences of unemployment, which include financial instability and increased dependency on external support. To overcome these challenges, the study recommends the government more intervention through job creation programs, financial support, more effort in vocational training, and formal and informal education. Additionally, further research should make more focus on sustainable employment and financial assistance programs. These findings can guide policymakers and stakeholders in addressing the unemployment issue and its financial burdens effectively.